Donor BMI >30 Is Not a Contraindication for Live Liver Donation. Issue 3 (19th September 2016) - Knaak, M.; Goldaracena, N.; Doyle, A.; Cattral, M. S.; Greig, P. D.; Lilly, L.; McGilvray, I. D.; Levy, G. A.; Ghanekar, A.; Renner, E. L.; Grant, D. R.; Selzner, M.; et al.
Abstract : The increased prevalence of obesity worldwide threatens the pool of living liver donors. Although the negative effects of graft steatosis on liver donation and transplantation are well known, the impact of obesity in the absence of hepatic steatosis on outcome of living donor liver transplantation (LDLT) is unknown. Consequently, we compared the outcome of LDLT using donors with BMI <30 versus donors with BMI ≥30. Between April 2000 and May 2014, 105 patients received a right‐lobe liver graft from donors with BMI ≥30, whereas 364 recipients were transplanted with grafts from donors with BMI <30. Liver steatosis >10% was excluded in all donors with BMI >30 by imaging and liver biopsies. None of the donors had any other comorbidity. Donors with BMI <30 versus ≥30 had similar postoperative complication rates (Dindo‐Clavien ≥3b: 2% vs. 3%; p = 0.71) and lengths of hospital stay (6 vs. 6 days; p = 0.13). Recipient graft function, assessed by posttransplant peak serum bilirubin and international normalized ratio was identical. Furthermore, no difference was observed in recipient complication rates (Dindo‐Clavien ≥3b: 25% vs. 20%; p = 0.3) or lengths of hospital stay between groups. We concluded that donors with BMI ≥30, in the absence of graft steatosis, are not contraindicated for LDLT. Abstract : Right lobe live liver donation can be performed safely in select obese patients in the absence of steatosis and donor comorbidities, which could open an interesting approach to further increase the donor pool.